IMPLEMENTASI STRATEGI TUTOR SEBAYA DALAM MENINGKATKAN KEMAMPUAN LITERASI MEMBACA SISWA KELAS 2 SDN BANGKOK - Ristiya Krisnawati; Robith Khoiril Umam (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
Reading literacy is a fundamental foundation for knowledge acquisition and academic success at the elementary school level. However, initial observations at SDN Bangkok revealed that most second-grade students still experienced difficulties in understanding reading content, identifying key information, and drawing conclusions from simple texts. This low literacy ability was mainly caused by teacher-centered learning methods and limited student engagement in meaningful learning activities. This study aims to improve students’ reading literacy skills through the peer tutoring strategy, which is based on Vygotsky’s socio-constructivist theory. The theory emphasizes that social interaction among peers can accelerate cognitive development through the zone of proximal development. In practice, students with better reading skills act as tutors for peers who face difficulties, creating an active, collaborative, and supportive learning environment. The research employed Classroom Action Research (CAR) using the STAR framework (Situation, Task, Action, Result). The Situation described the low reading literacy level; Task focused on improving it through peer tutoring; Action was implemented in two cycles; and Result showed a significant improvement in reading literacy and learning participation. The average score increased from 65.8 (pre-cycle) to 78.4 (cycle I) and 88.7 (cycle II), along with a 31.5% increase in participation. The findings prove that peer tutoring effectively enhances reading literacy, fosters positive social interaction, and builds students’ self-confidence.